Feeding Food Wastes to Swine - M. L. Westendorf; Robert O. Myer (EDIS, 2004)
The feeding of food waste or garbage to swine and other livestock animals is a common practice throughout the world and is often concentrated around metropolitan centers. Food plate waste (formerly referred to as garbage) may be fed to other livestock species, but has most often been used as a source of feed for swine. High disposal costs and fees encourage the feeding of food/plate waste. This document is AS143, one of a series of the Animal Science Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date May 17, 2004.